2015
DOI: 10.1210/en.2015-1786
|View full text |Cite
|
Sign up to set email alerts
|

Gene-by-Diet Interactions Affect Serum 1,25-Dihydroxyvitamin D Levels in Male BXD Recombinant Inbred Mice

Abstract: 1,25-Dihydroxyvitamin D (1,25[OH]2D) regulates calcium (Ca), phosphate, and bone metabolism. Serum 1,25(OH)2D levels are reduced by low vitamin D status and high fibroblast growth factor 23 (FGF23) levels and increased by low Ca intake and high PTH levels. Natural genetic variation controls serum 25-hydroxyvitamin D (25[OH]D) levels, but it is unclear how it controls serum 1,25(OH)2D or the response of serum 1,25(OH)2D levels to dietary Ca restriction (RCR). Male mice from 11 inbred lines and from 51 BXD recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Under normal conditions, blood 1,25(OH) 2 D levels are controlled by multiple mechanisms including genetic factors [27], blood IGF-1 levels [28, 29], blood FGF-23 levels [27], and blood 25(OH)D levels [29]. It has been shown that blood IGF-1 levels positively [28, 29] and blood FGF-23 levels negatively [27] correlate with blood 1,25(OH) 2 D levels. However, blood 25(OH)D levels do not correlate with blood 1,25(OH) 2 D levels [27, 30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under normal conditions, blood 1,25(OH) 2 D levels are controlled by multiple mechanisms including genetic factors [27], blood IGF-1 levels [28, 29], blood FGF-23 levels [27], and blood 25(OH)D levels [29]. It has been shown that blood IGF-1 levels positively [28, 29] and blood FGF-23 levels negatively [27] correlate with blood 1,25(OH) 2 D levels. However, blood 25(OH)D levels do not correlate with blood 1,25(OH) 2 D levels [27, 30].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that blood IGF-1 levels positively [28, 29] and blood FGF-23 levels negatively [27] correlate with blood 1,25(OH) 2 D levels. However, blood 25(OH)D levels do not correlate with blood 1,25(OH) 2 D levels [27, 30]. Blood 1,25(OH) 2 D levels change only when blood 25(OH)D levels change dramatically [30].…”
Section: Discussionmentioning
confidence: 99%
“…The BXD Family Is the Largest and the Most Deeply Phenotyped Mammalian Genetic Reference Panel Data sets for the BXD encompass multiple levels-from single molecules to complex behavioral repertoires and to traits measured with environmental perturbations, including exposure to alcohol and drugs of abuse (Dickson et al, 2019;Mulligan et al, 2018;ThĂ© berge et al, 2019;Zhou et al, 2018), infectious agents (Boon et al, 2014;Chella Krishnan et al, 2016;Russo et al, 2015), dietary modifications (Fleet et al, 2016;Jha et al, 2018bJha et al, , 2018aJones and Jellen, 2017;Reyes Fernandez et al, 2016;Rodrigues et al, 2017), stress (Diessler et al, 2018;Jung et al, 2017), and even as a function of age (Sandoval-Sierra et al, 2020;Williams et al, 2020). This phenome is linked to over 500 publications, including state-of-the-art proteome, metabolome (Williams et al, 2018(Williams et al, , 2020, epigenome (Baker et al, 2019;Sandoval-Sierra et al, 2019), and metagenome (Perez-Munoz et al, 2019) data sets available on GeneNetwork.org.…”
Section: Improved Power and Precision Of Mapping Bxd Phenotypes-a 50-year Path Of Progressmentioning
confidence: 99%
“…This phenome extends back to Taylor's (1973) analysis of cadmium toxicity, through to recent studies of metabolism (Roy et al, 2020;Wang et al, 2013Wang et al, , 2016bWilliams et al, 2016Williams et al, , 2020Wu et al, 2014), addiction (Dickson et al, 2016(Dickson et al, , 2019Mulligan et al, 2013), behavior (Carhuatanta et al, 2014;Graybeal et al, 2014;Mulligan and Williams, 2015;Philip et al, 2010), infectious disease (Hayes et al, 2014;McKnite et al, 2012;Wang et al, 2020), epigenetics (Baker et al, 2019; Sandoval-Sierra et al, 2020), and even indirect genetic effects (Ashbrook et al, 2015a(Ashbrook et al, , 2017Baud et al, 2017). BXDs have been used to test developmental and evolutionary hypotheses (Hager et al, 2012;Oren et al, 2015;Seecharan et al, 2003), to study GXE and consequences of treatments as a function of age, diet, and sex (Fleet et al, 2016;Philip et al, 2010;Roy et al, 2020;Sandoval-Sierra et al, 2020;Williams et al, 2016Williams et al, , 2020, gene pleiotropy (Wang et al, 2016a), and to test behavioral predictions based on differences in brain architecture (Yang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a possible hypothesis that could explain our findings would be that tissue damage in the kidneys and to a lesser extent in the lung caused by SARS-CoV2 may lead to an active decrease of 1,25(OH)D, responsible for the majority of biological actions of Vitamin D, but not in the form usually determined in plasma, Calcifediol. Previous studies showed that blood 25(OH)D levels may not correlate with blood 1,25(OH)2D levels in some clinical conditions [63][64][65].…”
Section: Discussionmentioning
confidence: 95%